Nitric oxide scavenging by cell-free hemoglobin may be a primary factor determining hypertension in polycythemic patients. (February 2014) - Rusak, T.; Misztal, T.; Piszcz, J.; Tomasiak, M.
Abstract: We tested the hypothesis that hypertension associated with polycythemia vera (PV) may be related to hemoglobin released from erythrocytes (cell-free hemoglobin, fHb). We assessed hematocrit, mean arterial pressure (MAP), blood viscosity, and the level of fHb and nitrite/nitrate (NOx ) in the plasma of 73 PV patients and 38 healthy controls. The effect of isovolemic erythrocytapheresis (ECP) on the considered parameters was also studied. From the whole group of PV patients a subset of subjects with normal (normotensive patients, n = 16) and elevated MAP (hypertensive patients, n = 57) can be subtracted. It was found that in comparison with healthy controls, PV patients have significantly (p ≤ 0.01) elevated Hct (0.567 vs. 0.422), blood viscosity (5.45 vs. 3.56 cP), MAP (106.8 vs. 93.8 mmHg), plasma fHb (9.7 vs. 2.8 mg/dL), and NOx levels (34.1 vs. 27.5 μM). Compared with normotensive patients, hypertensive PV patients demonstrated a higher rise in fHb (10.2 vs. 8.0) and plasma NOx levels (35.8 vs. 31.0). In PV patients, fHb positively correlates with MAP ( r = 0.489), NOx levels ( r = 0.461), hematocrit ( r = 0.428), and viscosity ( r = 0.393). Blood viscosity positively correlated with hematocrit ( r = 0.894), but not with other considered parameters. In PV patients MAP poorly correlated with hematocrit, whereas the correlation between MAP and NOx altered from − 0.325 (healthy control) to + 0.268 (PV patients). ECP procedure was associated with a significant ( p < 0.01) reduction of hematocrit, fHb, blood viscosity, and MAP. In the normotensive subgroup of PV patients the ECP procedure did not affect MAP. It can be concluded that accelerated scavenging of nitric oxide by fHb rather than high Hct may be a key factor determining the development of hypertension in PV patients.